Tungsten Disulfide Nanodispersions for Inkjet Printing and Semiconducting Devices. (10th May 2017) - Desai, Jay A.; Adhikari, Nirmal; Kaul, Anupama B.
ABSTRACT: In this work, we demonstrate optical and electrical transport properties of chemically exfoliated WS2 in cyclohexanone/ terpineol solvent using different sonication times. High electrical conductivity of WS2 nanodispersions was observed when appropriate amount of voltage was applied indicating their semi-conductive behavior. Surface morphology of WS2 nanodispersions sonicated at different times were studied using optical microscopy. Optical bandgap of WS2 nanodispersions were determined from optical absorbance spectrum. Inkjet printing was used to demonstrate uniform distribution of WS2 nanosheets and their precise and large scale printability. These dispersions indicate the potential of WS2 in various optoelectronic and semiconducting device applications.